The Synergistic Effect of Biosynthesized Copper Oxide Nanoparticles and Vancomycin on Biofilm Formation of Staphylococcus haemolyticus - Romi , Zahraa M.; E. Ahmed, Mais (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The results indicated that the biofilm formed by each Staphylococcus haemolyticus isolate was inhibited by 52%–82%. The highest value of biofilm formation (before treatment) was seen in the case of isolate A39, followed by A49 with absorption values of (1.382 and 1.116), respectively. Bacterial cells are capable of catalyzing the biosynthesis process by producing reductive enzymes. These green synthesized inorganic nanoparticles have been frequently investigated as possible bactericidal agents. Our findings revealed that at sub-Minimum Inhibitory Concentration (Sub-MIC), Copper oxide nanoparticles and Vancomycin combinations showed remarkable biofilm inhibitory outcomes in wild-type strains of Staphylococcus haemolyticus that are multidrug resistant. Strong biofilm producer strains were incubated with 100 µl of sub-MIC synergestic nanoparticles for 24 h at 37 ºC; the same strains showed weak biofilm production after incubation. This study was aimed at exploring whether synergistic green synthesized copper oxide nanoparticles and vancomycin combination can function as an anti-biofilm agent against Staphylococcus haemolyticus biofilm